Peran Perpustakaan Dalam Mengembangkan Institutional Repository di UIN Sunan Kalijaga Yogyakarta (IAIN Ponorogo, 2014)
This paper was written with the aim to determine the role of libraries in the development of Institutional Repository (IR) at UIN Sunan Kalijaga Yogyakarta. This is because IR is a unique collection owned by institutionand needs to be maintained and preserved. In addition, IR collections in digital library has also raised the name of the institution, achieved 10th rank in Indonesia for Webometrics repository in 2012, then rose to the rank 5 in 2013, and increased again to rank 3 by 2014. Role of the library become very important in the development of IR. Activities undertaken by the library is in terms of (1) collecting; (2) managing; (3) preserving; (4) evaluating; and (5) promoting.